Pengembangan Modul Transformasi Berbasis CORE (Connecting, Organizing, Reflecting, Extending) - Rahmatina Rahmatina; Laila Maharani; Abi Fadila; Bambang Sri Anggoro (Institut Agama Islam Negeri Curup, 2020)
This study aims to produce teaching materials in the form of CORE-based modules on geometry transformation materials and to determine the responses of students, educators to the modules developed and to determine the effectiveness of CORE-based modules on geometry transformation material. This research method is Research and Development (R&D) using the ADDIE model which consists of the stages Analysis, Design, Development, Implementation, Evaluation. Based on the result of the validation of the material expert and the module media are stated with the “proper” criteria. Student responses on a small scale and large scale (field), as well as educator responses to modules with criteria of attractiviness aspects “very interesting”. While the responses of educators to the modules developed obtained an average score of 4,42 with the criteria of attractiveness aspects “very interesting”. The results of the assessment of the effectiveness test obtained an N-Gain score of 0,694 with “moderate” qualifications. So teaching material in the form of CORE-based mathematics learning modules (Connecting, Organizing, Reflecting, Extending) on geometry transformation material is declared feasible, interesting, and effective to be used as teaching material in the learning process.